Analisis Penguatan Karakter Siswa Muslim di Sekolah Dasar Minoritas Melalui Pendidikan Agama Islam - Soedjiwo, Novena Ade Fredyarini (Journal of Islamic Education, 2023)
This study aims to strengthen the character of Muslim students in public elementary schools in Denpasar Bali through Islamic religious education, especially faith and morals and to analyze teaching materials in strengthening character in the material "Ayo Berperilaku Terpuji". The research method used is qualitative with a descriptive approach and supported by literature in analyzing character strengthening through PAI. The results of the research on strengthening the character of faith and morals through Islamic religious education of Muslim students at SD Negeri Denpasar. There are able to apply character strengthening through habituation carried out in class and school. Through the PAI teachers can provide an understanding of Islamic values to students, namely religion, tolerance, and harmony. While the analysis of teaching materials in strengthening character in the material "Ayo Berperilaku Terpuji", provides an understanding of character strengthening through pictures, comic stories, games and classroom practices. Through this character strengthening, students have a spirit of social behavior, empathy for the environment and foster active participation of peers and the environment.